Hydrogen as a Potential Fuel for the Shipping Industry (International Journal of Innovative Research in Engineering & Management, 2023)
Mobility is a socioeconomic concept, and  the demand for it is only going to grow in importance in  the foreseeable future. Clean, cost-effective, and  ecologically acceptable modes of transportation should be  used wherever possible. Hydrogen is an attractive  synthetic energy source for the transportation industry  because of its high gravimetric energy density and  availability in combined form throughout the world. In  contrast, its oxidation component somehow doesn't  contribute to greenhouse emissions, enabling it a potential  replacement to fossil fuels. Its economically practical  electricity generated by sustainable resources, on-board  collection to give a required driving range, employment  of long-lasting types of energy, and the construction of  infrastructures for its supply continue to be important  challenges. Using hydrogen energy source presents a  variety of environment related implications, which are  covered in this article. Recent developments in the  manufacturing, transport, administration, and transport of  hydrogen also are mentioned. This study finds that  nonrenewable sources now dominate hydrogen  manufacturing processes; nevertheless, improvements  and encouragement of the use of renewable sources for  hydrogen production are required in order to make it  completely sustainable.
Keywords: Biofuel; Energy; Fossil Fuel; Hydrogen; Transportation